Clinical Characteristics and Outcome of Arteriovenous Fistula among Patients Undergoing Haemodialysis with end Stage Renal Disease - Farhan Khan, Naveed Soomro, Iftikhar Ahmed, Shafique Ur Rehman, Usman Qamar, Zulfikar Ahmed, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the clinical characteristics and failure rate of arteriovenous fistula (AVF) among patients undergoing haemodialysis with end stage renal disease. Methodology: This was a cross-sectional study, done at department of urology at Bilawal Medical College for Boys, Liaquat University of Medial and Health Sciences Jamshoro Pakistan, with time duration of eleven months from April 2021 to February 2022. All the patients with age of more than 20 years, both genders, end stage renal disease and undergoing haemodialysis were included. The optimal site for fistula development was determined after taking blood pressure and completing the Allen test. Vascular diameter, intravascular thrombosis, arterial wall atherosclerosis, and the opening of arterial inflow and venous outflow access were all assessed during the procedure. End- to- side and side-to-side arteriovenous fistula were established if there were no contraindication. The patients were discharged after establishing the fistula's patency and experiencing the thrill. The patient's fistula patency and hemodialysis performance were assessed till six weeks. All the information was documented in the self-made proforma. SPSS version 26 was used for the data analysis. Results: A total of 100 cases were studied, most of the cases (49.0%) were more than 50 years old and males were most common 71.0%. Out of all, 59(59.0%) cases were diabetics and hypertensive. According to the site of arteriovenous fistulae (AVF), Left radio cephalic AVF was31.0%, left brachio cephalic AVF was 40.0%, left brachio basilic AVF 24.0%, right radio cephalic AVF 03.0%, right Brachio cephalic AVF 1.0% and right brachio basilic AVF 1.0%. At 6th week follow-up arteriovenous fistula was observed successfully functional in 91.0% cases, while 5.0% arteriovenous fistula were burst and in 3.0% it was failed, while one patient was died during this six-weeks follow-up. Conclusion: For haemodialysis, the arteriovenous fistula was observed to be the best and preferable option with higher functioning rate, noninvasive and lower complicated.